2009
DOI: 10.1016/j.rmed.2009.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of purified air administered to the breathing zone in allergic asthma: A double-blind randomized cross-over trial

Abstract: Clean air, administered directly to the breathing zone during sleep, can have a positive effect on bronchial inflammation and quality of life in patients with perennial allergic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 15 publications
2
40
0
2
Order By: Relevance
“…This study was designed to evaluate the effect of TLA on self-reported quality of life, and the small numbers of patients with acute asthma exacerbations during the study limited our power to evaluate whether TLA treatment reduces exacerbation rates. The effects of TLA on quality of life and FENO are consistent with previous pilot work using TLA 20. The clinical effects of nocturnal TLA treatment appear to be applicable to a broad patient group, because our study population included a wide age range of patients sensitised to a variety of perennial allergens, recruited in six countries.…”
Section: Discussionsupporting
confidence: 77%
“…This study was designed to evaluate the effect of TLA on self-reported quality of life, and the small numbers of patients with acute asthma exacerbations during the study limited our power to evaluate whether TLA treatment reduces exacerbation rates. The effects of TLA on quality of life and FENO are consistent with previous pilot work using TLA 20. The clinical effects of nocturnal TLA treatment appear to be applicable to a broad patient group, because our study population included a wide age range of patients sensitised to a variety of perennial allergens, recruited in six countries.…”
Section: Discussionsupporting
confidence: 77%
“…Three studies, one by Morris et al [34] and more recent ones by Pedroletti et al [35] and Stillerman et al [36•], looked at various HEPA SBZ filtration systems. Morris et al [34] studied the use of a laminar flow HEPA unit that could be positioned over the SBZ.…”
Section: Studies Of Portable Room and Sleep Breathing Zone Air Cleanersmentioning
confidence: 99%
“…The aim is to minimize the exposure to inhaled allergens and hence reduce the allergy-induced inflammation and improve disease control in atopic patients [100]. Two randomized double-blinded control studies on adults and children (from 7 years) with allergic asthma have shown improvement in disease-related quality of life and reduction in airways inflammation [101,102]. Subgroup analysis has showed the largest effect on patients with the most severe disease.…”
Section: Temperature-controlled Laminar Airflowmentioning
confidence: 99%